The Role of Communication in the Disbursement of Youth Enterprise Development Fund: A Case Study of Nyeri Town Constituency Youth Enterprise Scheme (C-Yes). - Mburu, Jinaro Paul; Ngugi, Dr. Muiru (International Journal of Communication and Public Relation, 2017)
Abstract Purpose: The study was an assessment of the role of communication in effective disbursement of Youth Enterprise Development Fund. The study also sought to establish the effectiveness of feedback mechanisms in CDAs offices and Youth Groups. The study further attempted to investigate whether communication gaps exist in CDA offices and Youth Groups. Finally, the study examined the effect of communication on the sustainable disbursement of Youth funds and performance of Youth Groups. Materials and methods: A descriptive survey research design was used. A questionnaire was used to collect data. A majority of the questions were closed ended and a few were open-ended. A population of 260 respondents was chosen, consisting of 200 youth groups and 60 CDAs. A sample size of 50% was chosen. The sample was 130 individuals divided into 100 youth groups and 30 CDAs. The data was analyzed using descriptive statistics. The tool for analysis was S.P.S.S; a Windows based statistical Package for social science. Presentation of the findings was done in tabulated and graphical formats. Results: Findings indicate that that there are different preferred channels of communication for the youths groups and the community development assistants. The preferred channels for both groups are use of telephone and sms, and may also use emails because these favour all the groups. The preferred channels for CDAs are face to face, and letters. The preferred channels of communication for the youth group leaders also included use of social media (Facebook and media). Findings also indicate that the feedback mechanisms between youth groups and CDAs are not effective and this may have a bearing on the successful disbursement of youth funds. Recommendations: The stakeholders are recommended to ensure that they use other channels other than face to face when communicating with youth leaders, the CDAs should also be encouraged to use social media as this may match the preferred channels of communication by youth group leaders. The stake holders are also recommended to use the channels of communication that suit both groups. Keywords: communication, disbursement, youth enterprise development fund